In vitro crevice corrosion of biodegradable magnesium in different solutions. (1st September 2020) - Chen, Bowei; Wu, Hongliu; Yi, Ruibang; Wang, Wenhui; Xu, Haidong; Zhang, Shaoxiang; Peng, Hongzhou; Ma, Junwei; Jiang, Haomiao; Zan, Rui; Qiao, Shuang; Sun, Yu; et al.
Abstract: Magnesium (Mg) is a promising biomedical metal because of its biodegradability. The crevice between tissue and Mg implant can not be neglected in some implantation sites due to inducing crevice corrosion of Mg. In this paper, a new single mold was designed to build the in vitro experimental setup and four kinds of solutions, i.e. the deionized water (DW), the 0.9 wt.% sodium chloride solution (NaCl), the phosphate buffer saline (PBS) and the modified simulated body fluid (m-SBF) were used to explore necessary factors of crevice corrosion in Mg. It was observed that crevice corrosion in Mg sheets would occur in NaCl and PBS solution under 0.2, 0.5 and 0.8 mm crevice thickness. And it was found that there were two necessary factors, i.e. chloride ion and crevice dimension, in crevice corrosion. For the high-purity Mg cannulated screws, crevice corrosion could occur inside tunnel when immersed in PBS.